OPTIMIZATION OF CASH WAQF MANAGEMENT IN THE ISLAMIC ECONOMIC REVIEW - Eka Junila Saragih (Journal of Islamic Economy and Business (JIsEB), 2023)
This study aims to examine the optimization of cash waqf management in which cash waqf is a productive waqf in developing the people's economy. In Indonesia, cash waqf that reaches trillions of rupiah has not been optimally managed or distributed to improve people's welfare. This research is a type of qualitative research using a literature review. Data collection is sourced from books, journals and laws and regulations. In Indonesia, cash waqf is still far behind other countries, including several neighboring countries in Southeast Asia. The waqf funds collected are around Rp. 831 billion from the potential waqf of Rp.180 trillion annually. This is due to the lack of public understanding of cash waqf, not many nazirs who are skilled in managing productive waqf and there is no integrated system in the use of cash waqf. Seeing this phenomenon, cash waqf needs to be re-optimized so that the development of the waqf runs smoothly and in accordance with expectations. The government or Islamic financial institutions must socialize about cash waqf, build the reputation of professional waqf institutions, and build an independent and professional waqf system.